2010
DOI: 10.1128/jb.00379-10
|View full text |Cite
|
Sign up to set email alerts
|

Catabolite Repression of the TodS/TodT Two-Component System and Effector-Dependent Transphosphorylation of TodT as the Basis for Toluene Dioxygenase Catabolic Pathway Control

Abstract: The TodS/TodT two-component system of Pseudomonas putida regulates the expression of the toluene dioxygenase (tod) operon for the metabolism of toluene, benzene, and ethylbenzene. The sensor kinase TodS has a complex domain arrangement containing two functional modules, each harboring a sensor and an autokinase domain separated by a receiver domain. The TodT protein is the cognate response regulator that activates transcription of the toluene dioxygenase (TOD) pathway genes at the P todX promoter. We report in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…CIB. Although carbon catabolite repression by organic acids had been reported in the aerobic catabolism of toluene in some bacteria ( Duetz et al, 1996 ; Ruíz et al, 2004 ; Busch et al, 2010 ), catabolite repression of the peripheral pathway for the anaerobic degradation of toluene has not been shown before.…”
Section: Resultsmentioning
confidence: 98%
“…CIB. Although carbon catabolite repression by organic acids had been reported in the aerobic catabolism of toluene in some bacteria ( Duetz et al, 1996 ; Ruíz et al, 2004 ; Busch et al, 2010 ), catabolite repression of the peripheral pathway for the anaerobic degradation of toluene has not been shown before.…”
Section: Resultsmentioning
confidence: 98%
“…Pseudomonas putida can use glucose and toluene for growth, and the use of both carbon sources has been extensively studied. The regulation of both catabolic pathways is tightly interwoven and characterized by simultaneous catabolite repression because glucose inhibits P todX expression, and toluene was found to affect glucose utilization (del Castillo and Ramos, ; Busch et al ., ). Glucose catabolism in P. putida occurs through three pathways that converge at the level of 6‐phosphogluconate, which is then metabolized by the Edd and Eda Entner/Doudoroff enzymes to central metabolites (Entner and Doudoroff, ; del Castillo and Ramos, ; del Castillo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It is an atypical histidine kinase composed of two supradomains, each containing a PAS 4 domain and a histidine kinase (HK) domain, which are separated by a response regulator receiver (RRR) domain ( 10 ). TodS lacks a transmembrane region ( 7 ), and its N-terminal PAS domain (PAS1) binds a wide range of effectors, including toluene, to trigger increased basal autophosphorylation of TodS, leading to a phospho-signal relay to TodT and ultimately transcriptional stimulation of the tod operon genes by interacting with phosphorylated TodT in the P tod X promoter region ( 11 14 ). A study demonstrated that the N-terminal PAS1 domain, the histidine kinase (HK1) His 190 residue, the central RRR Asp 500 residue, and the C-terminal histidine kinase (HK2) His 760 residue are all required for the multistep phospho-signal to the TodT Asp 57 residue ( 9 ).…”
Section: Introductionmentioning
confidence: 99%